Seismic response of partially saturated soils beneath shallow foundations under sequential ground motions - Zeybek, Abdülhakim; Madabhushi, Gopal Santana Phani; Pelecanos, Loizos (Springer, 2020)
Induced partial saturation is an innovative soil improvement technique intended to mitigate earthquake-induced liquefaction. Historical records indicate that successive earthquakes may occur in high seismic areas. Therefore, a comprehensive understanding of the response of partially saturated soils to sequential ground motions is of great significance for the rational design and execution of this method in engineering practice. In this study, a series of dynamic centrifuge experiments were conducted to investigate the impacts of sequential ground motions on the behavior of partially saturated soils beneath shallow foundations. Two different shallow foundation models with a bearing pressure of 135 kPa and 50 kPa were examined. Three seismic simulations, in order of increasing amplitudes, were sequentially applied to loosely-packed partially saturated sand models prepared with air injection technique. The assessment of the test results indicated that shallow foundations resting on saturated models of loose sand did suffer excessive settlements with each event, producing a large embedment of the foundation. However, much smaller settlements were recorded for partially saturated ground, and the level of the foundation embedment remained limited in this case. The deformation vector fields also indicated that different displacement mechanisms were observed for each successive event.
Zeybek, A.hakim/0000-0001-7096-5770
Keywords: Partially saturated soils; Shallow foundations; Successive earthquakes; Soil liquefaction; Air injection technique; Centrifuge modeling